Pelatihan Media Pembelajaran Berbasis Virtual/Digital sebagai Peningkatan Kompetensi Dosen - Ummul Hasanah; Muh. Rapi; Syahriani; Suhardiman; Andi Tenri Ola Rivai; Ayyub Ibrahim (Faculty of Tarbiyah and Teacher Training, 2022)
Training on the use of digital-based learning media aims to provide additional competence to lecturers in making new technology-based media. Subject service is a lecturer at the Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar as many as 12 participants with representatives from several study programs in the Faculty of Tarbiyah and Teacher Training UIN Alauddin. The data collection instrument uses a questionnaire that is distributed through a google form. As many as 75% of participants felt that this training was